Designing and Evaluating a User-Centered Cash Flow Monitoring Dashboard for Higher Education Using Design Thinking and UEQ Framework - Amalia; Rahmi Izzati; Bambang Harie Wiyono; R. Adhari Cahya Mahendra; Betty Amalia (Journal of Computer Networks, Architecture and High Performance Computing, 2026)
Although cash flow monitoring dashboards have been widely implemented in higher education institutions, existing studies predominantly focus on technical development or usability testing, with limited attention to how user-centered design frameworks contribute to financial decision-making effectiveness. This creates a research gap regarding the systematic application of design thinking as a methodological approach for developing and evaluating financial dashboards in university contexts. This study addresses this gap by proposing and evaluating a user-centered cash flow monitoring dashboard developed using a design thinking approach. A descriptive quantitative method was employed through a case study conducted at Sekolah Tinggi Teknologi Terpadu Nurul Fikri. Data were collected through stakeholder interviews and prototype evaluation using the User Experience Questionnaire (UEQ). The design thinking process was implemented across the empathize, define, ideate, prototype, and test stages to ensure alignment between user needs and dashboard functionality. The findings indicate that the proposed dashboard achieved strong performance across key UEQ dimensions, particularly attractiveness, efficiency, and dependability, demonstrating its effectiveness in supporting cash flow monitoring and managerial financial decision-making. Unlike previous studies that emphasize system implementation outcomes, this research provides empirical insights into how design thinking facilitates the translation of user needs into actionable financial information. This study contributes to the literature by offering a structured framework for applying design thinking in the development of financial monitoring dashboards within higher education institutions. The results also have practical implications for universities seeking to improve data-driven financial governance through user-centered financial information systems.